A construção simbólica do “mártir da caminhada latino-americana” - Filho, José Reinaldo Felipe Martins (Revista eclesiástica brasileira, 2021)
This article aims to identify in the minutes of martyrdom of Father João Bosco Penido Burnier, produced by Bishop Pedro Casaldáliga, the symbolic elements that make up a murderer as a Martyr of the Latin American Walk. Unlike martyrs because of faith, these – called martyrs of justice, or jesuanic – are identified with Jesus and die like him, in defense of His causes: life, justice, freedom, human rights and so on. Through the analysis of literary and plastic records about martyrdom in Latin American theology, especially that related to the Prelature of São Félix do Araguaia, confronted with theories about the symbolic, we were able to point out some conclusions. Namely: the symbolic elements used in the characterization of the martyr of the walk by Casaldáliga in the minutes of Burnier’s martyrdom seem to be intentional. But what are your intentions? Among other possibilities, it can be answered: animate the struggles for which many died, keep the memory of the dead alive, transpose the struggles from the material field to the religious field and condense collectives around the memory of a murdered leadership. From the religious point of view, the giving of life is the maximum expression of the configuration of a life to Jesus in announcing the Kingdom of God and in denouncing the anti-kingdom.